2015
DOI: 10.1101/026088
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genetic evidence challenges the native status of a threatened freshwater fish (Carassius carassius) in England

Abstract: A fundamental consideration for the conservation of a species is the extent of its native range, that is, regions naturally colonized. However, both natural processes and human-mediated introductions can drive species distribution shifts. Ruling out the human-mediated introduction of a species into a given region is vital for its conservation, but remains a significant challenge in most cases. The crucian carp Carassius carassius (L.) is a threatened freshwater fish thought to be native to much of Europe.Howev… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 62 publications
0
20
0
Order By: Relevance
“…The species included in the list of translocated freshwater fishes encompassed: A) all native species that are known to have been introduced from their native distribution range in GB to other parts of GB where the species is not native; and B) any other native species likely to be translocated within GB. Note that in the case of crucian carp Carassius carassius, the RA area encompasses all parts of GB because a recent genetic study has demonstrated that this species was most likely introduced about the same time as common carp Cyprinus carpio, and therefore is most likely 'not native' to southeast England as was previously believed by some scientists (Jeffries et al, 2017). A similar approach, encompassing both extant and potential future species, has been used in all published applications of AS-ISK on freshwater fishes to date (i.e., Glamuzina et al, 2017;Li et al, 2017; and in most previous applications of FISK (see Copp, 2013), as this provides a means of assessing current species, which may or may not have expressed invasive patterns.…”
Section: Methodsmentioning
confidence: 99%
“…The species included in the list of translocated freshwater fishes encompassed: A) all native species that are known to have been introduced from their native distribution range in GB to other parts of GB where the species is not native; and B) any other native species likely to be translocated within GB. Note that in the case of crucian carp Carassius carassius, the RA area encompasses all parts of GB because a recent genetic study has demonstrated that this species was most likely introduced about the same time as common carp Cyprinus carpio, and therefore is most likely 'not native' to southeast England as was previously believed by some scientists (Jeffries et al, 2017). A similar approach, encompassing both extant and potential future species, has been used in all published applications of AS-ISK on freshwater fishes to date (i.e., Glamuzina et al, 2017;Li et al, 2017; and in most previous applications of FISK (see Copp, 2013), as this provides a means of assessing current species, which may or may not have expressed invasive patterns.…”
Section: Methodsmentioning
confidence: 99%
“…Conservation organisations (e.g. English Nature, Environment Agency) later recognised the crucian carp as native and threatened (Environment Agency, ; Smith & Moss, ), but recent genetic evidence supports anthropogenic introduction of the crucian carp to the UK during the 15th century (Jeffries et al., ). Nonetheless, many introduced species in the UK are now naturalised, and several provide ecological and economical benefits (Manchester & Bullock, ).…”
Section: Introductionmentioning
confidence: 99%
“…Three pooled populations were considered in this step, based on the three STRUCTURE‐defined groups: NE, TU (TU_AK and TU_NI), and CORE (UK, US_CA, US_OR, AU, GE, and IR). Pooling populations with shared history is an efficient way to reduce the complexity of candidate scenarios and has been used in numerous other studies (see Pedreschi et al, ; Jeffries et al, ). Six evolutionary scenarios that considered population history events including divergence, admixture, and population size variation were evaluated.…”
Section: Methodsmentioning
confidence: 99%